2001
DOI: 10.1111/j.1348-0421.2001.tb02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Lactobacillus casei Group and the Lactobacillus acidophilus Group by Automated Ribotyping

Abstract: A total of 91 type and reference strains of the Lactobacillus casei group and the L acidophilus group were characterized by the automated ribotyping device Riboprinter" microbial characterization system. The L. casei group was divided into five

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Based on our preliminary results, we suspected that these strains do not belong to L. acidophilus (group A1). Furthermore, data from a recent study by Ryu et al (2001), who used a ribotyping technique, confirmed the results of a previous study that showed that the L. acidophilus group could be divided into two major clusters. Noticeably, the results also showed that the L. acidophilus group could be further divided by ribotyping into 14 genotypes (A1-A11 and B1-B3) with similarity levels of 50 % and that JCM 1038 and JCM 1039 belong to an independent genotype among the 14 genotypes.…”
supporting
confidence: 77%
“…Based on our preliminary results, we suspected that these strains do not belong to L. acidophilus (group A1). Furthermore, data from a recent study by Ryu et al (2001), who used a ribotyping technique, confirmed the results of a previous study that showed that the L. acidophilus group could be divided into two major clusters. Noticeably, the results also showed that the L. acidophilus group could be further divided by ribotyping into 14 genotypes (A1-A11 and B1-B3) with similarity levels of 50 % and that JCM 1038 and JCM 1039 belong to an independent genotype among the 14 genotypes.…”
supporting
confidence: 77%
“…Within the L. casei group (group III), several methods distinguished the group members, including assessment of sequence variations in the 16S rRNA gene (ribotyping) (28) and the 16S-23S rRNA ISR (35). Alternative single-locus targets for phyloge-netic classification of lactobacilli include tuf, the gene encoding elongation factor Tu (3).…”
Section: Discussionmentioning
confidence: 99%
“…With 16S rRNAbased phylogenetic analysis, at least eight phylogenetic groups have been recognized (10). Investigations by many authors using several molecular approaches focused on closely related species, such as the L. casei-related taxa (6,9,12,38,44,47,57,61), the L. acidophilus group (19,32,41,45,47), the L. delbrueckii subspecies (20,35,36,56), and the L. plantarum-related species (54). Nevertheless, the discrimination of very closely related species, especially of subspecies, is often critical (10).…”
mentioning
confidence: 99%